Development of Proximity Sensor-Based Mathematical Pendulum Experiment Modeling Tool for Video Tracker Analysis - Yosi, Yosi; Asrizal, Asrizal (Journal of Experimental and Applied Physics, 2025)
Physics has an important role in the development of science and technology today. One of the interesting motion phenomena in physics is simple harmonic motion on a mathematical pendulum. Physical phenomena can be observed through experiments using research instruments. The observation shows that the data of the mathematical pendulum experiment is only limited to the oscillation time and the number of swings. In addition, the instruments used are still manual. One solution to overcome these problems is to use a proximity sensor-based mathematical pendulum experiment modeling tool and video analysis using a tracker. The purpose of this research is to determine the accuracy and precision of the mathematical pendulum modeling tool experiment, knowing the effect of changes in rope length on the period and frequency of the mathematical pendulum modeling tool. This research is a type of design and development research (Research and Development). Data collection was carried out with two events, namely direct and indirect measurements. Direct measurements are made by varying the length of the rope on the mathematical pendulum experiment modeling tool. Indirect measurements are made to determine the accuracy and precision of the proximity sensor-based mathematical pendulum modeling tool. The results of the data analysis obtained are displayed in the form of tables and graphs. Based on the data analysis, three research results can be stated. First, video analysis using a tracker obtained a sinusoidal graph. Second, the average accuracy and precision of the modeling tool are period 99.50% and 96.66%, frequency 99.68% and 96.47%, and acceleration of gravity 99.20% and 95.50%. Third, the longer the rope used, the greater the period obtained, which is inversely proportional to the smaller frequency.